Visualization and quantification of nascent RAD51 filament formation at single-monomer resolution - Candelli, Andrea; Holthausen, Jan Thomas; Depken, Martin; Brouwer, Ineke; Franker, Mariëlla A M; Marchetti, Margherita; Heller, Iddo; Bernard, Stéphanie; Garcin, Edwige B; Modesti, Mauro; Wyman, Claire; Wuite, Gijs J L; et al. (Proceedings of the National Academy of Sciences - PNAS, 2014)
During recombinational repair of double-stranded DNA breaks, RAD51 recombinase assembles as a nucleoprotein filament around single-stranded DNA to form a catalytically proficient structure able to promote homology recognition and strand exchange. Mediators and accessory factors guide the action and control the dynamics of RAD51 filaments. Elucidation of these control mechanisms necessitates development of approaches to quantitatively probe transient aspects of RAD51 filament dynamics. Here, we combine fluorescence microscopy, optical tweezers, and microfluidics to visualize the assembly of RAD51 filaments on bare single-stranded DNA and quantify the process with single-monomer sensitivity. We show that filaments are seeded from RAD51 nuclei that are heterogeneous in size. This heterogeneity appears to arise from the energetic balance between RAD51 self-assembly in solution and the size-dependent interaction time of the nuclei with DNA. We show that nucleation intrinsically is substrate selective, strongly favoring filament formation on bare single-stranded DNA. Furthermore, we devised a single-molecule fluorescence recovery after photobleaching assay to independently observe filament nucleation and growth, permitting direct measurement of their contributions to filament formation. Our findings yield a comprehensive, quantitative understanding of RAD51 filament formation on bare single-stranded DNA that will serve as a basis to elucidate how mediators help RAD51 filament assembly and accessory factors control filament dynamics.